2017
DOI: 10.1253/circj.cj-16-1109
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endovascular Repair of Aortoiliac Aneurysms and Analyses of Anatomic Suitability for Internal Iliac Artery Preserving Devices in Japanese Patients

Abstract: Background Understanding common iliac arteries (CIA) are shorter in Asian patients, we investigated whether this anatomical difference affects clinical outcomes of internal iliac artery (IIA) exclusion during endovascular repair (EVAR) of aorto-iliac aneurysm and limits the use of IIA preserving devices in Japanese patients. Methods and Results From 2008–2014, 69 Japanese patients underwent EVAR of aorto-iliac aneurysms with 53 unilateral and 16 bilateral IIA exclusion. One patient had persistent-buttock cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
2
14
1
3
Order By: Relevance
“…23,24 The only problem with these iliac branch devices is that they can be accommodated by only approximately 30% of the population, when the IFU of these devices is strictly obeyed. 25,26 On the other hand, deployment of a stent-graft limb in the EIA is feasible for all types of patient anatomy, and we were able to demonstrate that buttock claudication associated with the procedure improved and almost diminished during the follow-up, just as in previous literature. 25…”
Section: Operative Resultssupporting
confidence: 71%
“…23,24 The only problem with these iliac branch devices is that they can be accommodated by only approximately 30% of the population, when the IFU of these devices is strictly obeyed. 25,26 On the other hand, deployment of a stent-graft limb in the EIA is feasible for all types of patient anatomy, and we were able to demonstrate that buttock claudication associated with the procedure improved and almost diminished during the follow-up, just as in previous literature. 25…”
Section: Operative Resultssupporting
confidence: 71%
“…1) Another study reported that 24% of Japanese patients with aorto-iliac aneurysms were excluded because the AOL was too short for the device size. 2) Taking other anatomical factors into account, only 40% of patients could be treated by these devices. 2) In the case of insufficient common iliac length, even if the AOL was sufficient, the IBE can be used with the proximal end of the device located in the AAA, and the internal iliac component could be deployed using brachial or axillar access.…”
Section: Discussionmentioning
confidence: 99%
“…2) Taking other anatomical factors into account, only 40% of patients could be treated by these devices. 2) In the case of insufficient common iliac length, even if the AOL was sufficient, the IBE can be used with the proximal end of the device located in the AAA, and the internal iliac component could be deployed using brachial or axillar access. 9) However, with insufficient AOL, there seemed to be no alternative option but to modify the DIL in some way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of IBE in maintaining perfusion to the internal iliac arteries while treating iliac aneurysms or tybe 1b endoleaks following EVAR has been demonstrated by multiple studies. [1][2][3] As a result of the mounting evidence of pelvic ischemic complications and the quality of life implications for patients suffering from buttock claudication or erectile dysfunction following hypogastric artery embolization, maintaining internal iliac artery perfusion following EVAR is becoming increasingly common. [6][7][8] In patients with a previous EVAR, however, maintaining internal iliac perfusion with an IBE is technically challenging given the new anatomic constraints created by the endograft.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%